Institutional ethnography of hemodialysis care: Perspectives of multidisciplinary health care teams in Nepal - Devaka Kumari Acharya; Kittikorn Nilmanat; Umaporn Boonyasopun (Belitung Nursing Journal, 2023)
Background: Hemodialysis is the most commonly used renal replacement therapy for end-stage renal disease. The collaborative efforts of multidisciplinary teams comprising nephrologists, nurses, pharmacists, and dietitians play a crucial role in enhancing patient outcomes, improving the quality of care, and reducing treatment costs. However, various factors such as healthcare cost reduction, limited resources, profit-driven systems, organizational structure, and involvement in patient care decisions impact the provision of hemodialysis care by the multidisciplinary teams.   Objective: This study aimed to explore the institutional practices of multidisciplinary teams within a hemodialysis unit. Methods: This institutional ethnography study was conducted between April 2019 to February 2020 in a hemodialysis unit of a public university hospital in Kathmandu, Nepal. Data were collected through face-to-face interviews with ten nurses (including supervisors and incharge), two nephrologists, two dietitians, two pharmacists, and two technicians. Additionally, 167 hours of observation, two focus groups with nurses, analysis of institutional texts, and field notes were conducted. Participants were purposively selected based on their ability to provide diverse information regarding institutional practices in hemodialysis care. Interviews were recorded and transcribed. Results: The analyzed data were presented in: 1) the context of hemodialysis care, 2) textual practices: the ruling relations of hemodialysis care (staffing, protocol, job description), 3) hemodialysis decision, and 4) institutional support. Conclusion: Hemodialysis care provided by multidisciplinary teams is constrained by limited resources, particularly in terms of physical space, dialysis machines, nurses, doctors, and dietitians. The hospital's cost-cutting policies lead to reduced investment in patient care equipment, particularly dialysis machines, which significantly impact the workload of nurses and technicians. Insufficient nurse staffing necessitates the provision of other renal care responsibilities, resulting in increased workload, reduced time available for hemodialysis care, and unfinished tasks. The absence of clear job descriptions for hemodialysis care places an additional burden on nurses, who are often required to fulfill the responsibilities of other healthcare teams. Doctors hold the authority in making care decisions, which are subsequently followed by other team members.